Integrating the cost of the carbon footprint within the income statement: Tests on seven Polish firms - Christophe Cathala (Financial Internet Quarterly, 2021)
Purpose: Even if popular, carbon accounting is not yet compulsory for companies. However, it should be and certainly will be. From the state's point of view, this will be a prerequisite to respecting its international commitments. From the point of view of companies, it is also neces-sary because they use, in part for free, limited resources to create value-added [...] and they gen-erate externalities which are not yet fully measured and communicated. Our purpose is to propose a relatively new metric, which is quite simple and could be applied to all companies, especially small ones (turnover < EUR 10 million). Design/methodology/approach: Our metric in this paper is linked to the income statement and measurement of the output of carbon used in the production process of goods and/or services. We compare the use of carbon by seven Polish companies in seven different sectors from 2014 to 2020. The metric is computed in the same way for the firms in our sample and is based on information which must be stated on the yearly income statement. Findings: From our empirical tests, we observe that comparison can first be made between firms and sectors. As expected, the impact is far more important for industries than for service compa-nies. In terms of volatility, we reach the same result. However, this volatility is not linked to the nature of the companies but more to the volatility of the carbon price. As a first step, this gives an interesting and rough measure of the cost of the carbon emission per company per year.
Keywords: H25; H23; M41; 330; carbon accounting; income statement; carbon cost; carbon footprint